Elaboration and Innervation of the Vibrissal System in the Rock Hyrax (Procavia capensis) - Sarko, Diana K. (Brain Behav Evol, 2015)
Mammalian tactile hairs are commonly found on specific, restricted regions of the body, but Florida manatees represent a unique exception, exhibiting follicle-sinus complexes (FSCs, also known as vibrissae or tactile hairs) on their entire body. The orders Sirenia (including manatees and dugongs) and Hyracoidea (hyraxes) are thought to have diverged approximately 60 mya, yet hyraxes are among the closest relatives to sirenians. We investigated the possibility that hyraxes, like manatees, are tactile specialists with vibrissae that cover the entire post-facial body. Previous studies suggested that rock hyraxes possess post-facial vibrissae in addition to pelage hair, but this observation was not verified through histological examination. Using a detailed immunohistochemical analysis, we characterized the gross morphology, innervation, and mechanoreceptors present in FSCs sampled from facial and post-facial vibrissae body regions to determine that the long post-facial hairs on the hyrax body are in fact true vibrissae. The types and relative densities of mechanoreceptors associated with each FSC also appeared to be relatively consistent between facial and post-facial FSCs. The presence of vibrissae covering the hyrax body presumably facilitates navigation in the dark caves and rocky crevices of the hyrax's environment where visual cues are limited, and may alert the animal to predatory or conspecific threats approaching the body. Furthermore, the presence of vibrissae on the post-facial body in both manatees and hyraxes indicates that this distribution may represent the ancestral condition for the supraorder Paenungulata.